A brief overview of the portuguese agriculture – its evolution, performance and current situation - Marques, Carlos (2015)
Abstract: In 2016 passes the thirty anniversary of the entrance of Portugal to the European Union, at the time the EEC (European Economic Community). This article is a brief and broad overview of the Portuguese agriculture and of its evolution, performance and current situation, within that temporal context. A characterization of Portuguese agriculture and its importance for the country is presented. Major factors that characterize its performance over recent times and the current situation, such as general and historical setting, climate and environment, agricultural structural and socio-economic characteristics, development of rural areas, trade balance, agricultural and rural development policies, are reviewed to give a broad perspective of its evolution.